ANALISIS KESULITAN MEMBACA PERMULAAN BAGI SISWA KELAS 1 SD NEGERI 38 KOTA SORONG - Jacoba Samusamu; Asrul Asrul; Muhamad Faizin (CV. ADIBA ASIHA AMIRA, 2025)
Reading is a receptive language skill and is very important for life, meaning that reading brings someone to receive information from the activity. Beginning reading is one aspect of language skills that lasts for two years for the first and second grades of elementary school. Reading difficulties in lower grade students are quite numerous, there are still many students who do not know letters, have difficulty distinguishing letters, do not know diphthongs and consonants. This study aims to determine what are the beginning reading difficulties and the factors that influence students' reading difficulties. This study uses a descriptive qualitative research method. Qualitative research is used to understand the subjects studied about the causes of reading difficulties experienced by the subjects and the influence of reading difficulties on the scores of each subject. Based on the results of observations of 25 grade I students at SD Negeri 38 Sorong City, 8 students were identified as unable, 10 were quite able and 7 were able. There are several factors why students experience reading difficulties including low ability and interest of students in learning activities, family and environmental factors.